Acalypha wilkesiana - Edward F. Gilman (EDIS)
This large, fast-growing evergreen shrub provides a continuous splash of color in the landscape. The bronze red to muted red 4- to 8-inch-long, heart-shaped leaves are available in varying mottled combinations of green, purple, yellow, orange, pink, or white, depending upon cultivar (Figure 1). These colors make copperleaf difficult to blend into the landscape. Two or three shrubs are usually sufficient for specimen or accent plantings. Be careful not to over-plant with copperleaf. Their unusual color attracts attention and they could look gaudy. The dense, much-branched growth habit creates a full shape, but plants occasionally need shaping to maintain a neat appearance. The upright growth of copperleaf can reach 10 to 15 feet in height, making it well-suited to use as an accent in mixed shrubbery borders. Upright and side branches eventually droop and the plant can spread to about 8 feet wide. The unusual, red, fuzzy, catkin-like flowers hang pendulously from leaf axils and are 8 to 12 inches long. It has been used as a hedge or screen planted on 3- to 5-foot centers. This document is Fact Sheet FPS-6, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and and Agricultural Sciences, University of Florida. Publication date: October 1999; reviewed October 2003.